Multi-system endocrine disruption - Bourguignon, Jean-Pierre (Research and Perspectives in Endocrine Interactions, 2011)
Endocrine disruption is an expanding field due to the numerous chemicals involved and, as evidenced more recently, the variety of homeostatic systems that they can alter throughout life. The gathering of experts from all over the world should help to identify health disorders that are possibly or likely related to exposure to endocrine disrupters. The research needs have been discussed as well as recommendations prioritizing target groups and following the precautionary principle.